An analytical study of the reality of blended learning for practical lessons in volleyball in colleges and departments of physical education and sports sciences in baghdad - Alyaa Talib (الرياضة المعاصرة, 2021)
The aim of the research is to prepare a questionnaire about the reality of blended learning for practical lessons in volleyball in colleges and departments of physical education and sports sciences in baghdad and to identify the strengths and weaknesses of the blended learning in this type of blended learning in baghdad from the point of view of the faculty members and the descriptive approach was adopted in a case study style on a sample of (61) faculty members who teach volleyball in blended learning in the faculties and departments of physical education and sports sciences for baghdad ALMustansiriya and AL-Iraqiya universities who are on duty for the academic year (2020/2021) all of them were deliberately selected for the total research sample with a percentage of (100%) and then they were divided into three samples according to the requirements of the research and processing the results using the (spss) system to be the conclusions and applications in that the blended learning techniques achieve the educational goals for learning volleyball skills but they do not achieve the interaction required by the teaching process between the learner and the teacher and the learners benefit from the continued survival of the videos teaching volleyball in the international information network and from the attached theoretical file of their recorded lectures teaching volleyball on the platforms E-learning is part of blended learning but they need to feel satisfied when they are taught by blended learning and blended learning saves teachers a lot of time by reducing the explanation to the practical attendance lessons for teaching volleyball but they are not satisfied with the evaluation because they believe that it is unfair in blended learning and they do not support continuing blended learning when teaching volleyball in the future and it is necessary that the parties that called for blended learning provide all the technical requirements and what this type of learning needs and it is necessary to spread a culture of blended learning productivity in normal and emergency conditions and improve the capabilities of teachers in practical lessons when applied it is necessary to create highly efficient committees to enable blended learning and its effectiveness for both the teacher and the learner in teaching practical lessons in the faculties and departments of physical education and sports sciences